2019
DOI: 10.3389/fnins.2019.00497
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Melanopsin and Trigeminal Neural Pathways in Blue Light Photosensitivity in vivo

Abstract: Photophobia may arise from various causes and frequently accompanies numerous ocular diseases. In modern highly illuminated world, complaints about greater photosensitivity to blue light increasingly appear. However, the pathophysiology of photophobia is still debated. In the present work, we investigated in vivo the role of various neural pathways potentially implicated in blue-light aversion. Moreover, we studied the light-induced neuroinflammatory processes on the ocular surface and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 66 publications
(103 reference statements)
0
31
0
Order By: Relevance
“…Another possible explanation for the presence of persistent corneal damage after cataract surgery may be involved altered corneal mechanosensitivity mediating intrinsically photosensitive retinal ganglion cells (ipRGCs) [24,25]. With the existence of melanopsin, ipRGCs respond to light in the absence of rod and cone photoreceptor input.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible explanation for the presence of persistent corneal damage after cataract surgery may be involved altered corneal mechanosensitivity mediating intrinsically photosensitive retinal ganglion cells (ipRGCs) [24,25]. With the existence of melanopsin, ipRGCs respond to light in the absence of rod and cone photoreceptor input.…”
Section: Discussionmentioning
confidence: 99%
“…With the existence of melanopsin, ipRGCs respond to light in the absence of rod and cone photoreceptor input. [26] IpRGCs project in the ciliary marginal zone [27] and iris [28], mediating innate light aversion into tissues in the anterior segments that receive trigeminal innervation [25]. Although melanopsin absorbs blue light with a peak absorption of approximately 460 to 480 nm [29,30], previous studies have reported a significant increase in blue light transmission and subsequent ipRGC activation in both blue-light blocking IOLs and clear IOLs after cataract surgery [31].…”
Section: Discussionmentioning
confidence: 99%
“…These findings collectively indicate that the afferent arm of the light-induced lacrimation reflex pathway is melanopsin-mediated and that it functions normally in participants with migraine. Although it is plausible that the newly identified melanopsin-containing trigeminal fibers [ 36 38 ] may contribute to the light-induced lacrimation we observed, their contribution was eliminated or minimized during our experiment because the ocular surface was anesthetized with the use of topical proparacaine, which acts as an antagonist to voltage-gated sodium channels.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, bright light activates the trigeminal ganglion and trigeminal nucleus caudalis [73][74][75] . Human studies suggest an interaction of the peripheral trigeminal system and light-mediated pathways, as noxious trigeminal stimulation lowers the visual discomfort threshold, and light stimulation lowers trigeminal pain thresholds 11,76 .…”
Section: The Neural Locus Of Amplificationmentioning
confidence: 99%